(untitled) (Cardiovascular Journal, 2015)
Background: Aim of our study was to predict the effect of subvalvular changes on mitral valve leaflets excursion in a patient with mitral stenosis following percutaneous trans-venous mitral commissurotomy. Methods: Total of 60 patients of severe mitral stenosis were enrolled in the study. Transthoracic echocardiography was done on the day before percutaneous trans-venous mitral commissurotomy and 24-48 hours after percutaneous trans-venous mitral commissurotomy. Subvalvular area, anterior and posterior leaflets excursion were recorded. Results: Following percutaneous trans-venous mitral commissurotomy there were significant increase in anterior leaflet excursion from 1.8 ± 0.2 to 2.2 ± 0.2cm (p=<0.001), posterior leaflet excursion from 1.5±0.2to1.8 ± 0.2cm (p<0.001) . Subvalvular splitting areas was from 0.8 ± 0.2 to1.2 ± 0.2cm²(p=<0.001). Pulmonary arterial systolic pressure and left atrial diameter were significantly reduced respectively 55.6 ± 19.5 vs. 31.6 ± 9.5 mmHg,(p < 0.001) and 4.3 ± 0.6 cm vs. 3.8 ± 0.6 cm (p < 0.001). Post percutaneous trans-venous mitral commissurotomy subvalvular splitting area was found to be the predictor of increased excursion of both anterior and posterior mitral leaflets. Conclusion: percutaneous trans-venous mitral commissurotomy is associated with immediate significant changes in mitral valve morphology in terms of splitting of fused mitral commissures, increased valve leaflets excursion and splitting of the subvalvular structures. Post percutaneous trans-venous mitral commissurotomy subvalvular splitting area was found to be the predictor of increased excursion of both anterior and posterior mitral leaflets. Cardiovasc. j. 2015; 8(1): 8-12